A choice experiment versus a continent valuation approach to elicit the value of clean air in Singapore - Won, Isabel Ling Min (2017)
This study aims to estimate Singaporeans’ valuation of clean air through the Contingent Valuation Method (CVM) as well as Choice Experiment (CE) method. This is executed through asking respondents their (i) Willingness to Pay (WTP) for improvement in the current air quality, (ii) Willingness to Accept (WTA) to live in a more polluted environment and (iii) Preferred alternative with different attributes within each choice set. Furthermore, comparison between CVM and CE method is done to obtain the value of clean air in Singapore with the least potential bias which can be a guide for future policymaking. It is concluded that the CE method has the least potential bias when eliciting the value of clean air in Singapore. This is because CE (i) provides more information as respondents can choose among different alternatives with different levels of attributes (ii) eliminates the problem of starting point bias and (iii) minimises the possibility of protest bids. From the results, the estimated total WTP per year for the mitigation of motor vehicle emissions, transboundary haze and natural gas emissions are SGD 1.29 billion, SGD 787 million and SGD 1.86 billion respectively. These estimates are large enough to make improvements in the air quality of Singapore and can be used as a guide for future policy implementations.